Integration of the Tahfidz Curriculum and the Madrasah Curriculum in Grade 1 at MITQ Jamilurrahman: A Qualitative Descriptive Study - M. Husni Arsyad; Bagas Irawan; Dendi Fitriansyah; Musthafa Ahyar Muttaqin; Lalu Ali Hasan; Akmal Fathoni Hastadi (FKIP - Universitas Riau, 2026)
This study examines the planning, implementation, and learning outcomes of an integrated Tahfidz and madrasah curriculum in Grade 1 at Madrasah Ibtidaiyah Tahfidzul Qur’an (MITQ) Jamilurohman. Using a qualitative descriptive approach, data were collected through in-depth interviews, classroom observations, and documentation, and analyzed using the Miles and Huberman interactive analysis model. The findings indicate that curriculum integration is implemented through systematic coordination among Tahfidz teachers, curriculum coordinators, and school leadership. Qur’an memorization is positioned as a foundational learning activity that is intentionally integrated with academic instruction in daily learning practices. This integrated approach contributes to the development of disciplined learning behavior, positive learning habits, strong attachment to the Qur’an, and stable academic achievement among students. The results suggest that curriculum integration not only supports spiritual and moral development but also maintains academic learning effectiveness at the elementary level. Overall, this study provides empirical evidence that an integrated Tahfidz-based curriculum can serve as an effective model for holistic Islamic elementary education.